Claude Crébillon et l'île des plaisirs - Ana Alexandra Seabra de Carvalho (Carnets)
Known in his time as « physicist of love » or « philosopher of women », Claude Crébillon (1707-1777) is an author surrendered to the pleasure of writing and master of an incomparable style that seduced his reader and invites him to complex interpretation games. In this study, we will approach L’Écumoire, a gallant tale of supposedly oriental inspiration, in which the young author devotes himself to the problematization of the marvellous genre and gallant libertinism, namely in making the most of the context of the seductive Île Jonquille.